Aerosol deposited BaTiO3 film based interdigital capacitor and squared spiral capacitor for humidity sensing application. Issue 1 (1st January 2021) - Kumar, Alok; Wang, Cong; Meng, Fan-Yi; Liang, Jun-Ge; Xie, Bing-Fang; Zhou, Zhong-Liang; Zhao, Meng; Kim, Nam-Young
Abstract: In this article, ultra-high sensitive aerosol deposited BaTiO3 film based inter-digital capacitors (IDCs), and a squared spiral capacitor (SSC) have been investigated for humidity sensing application. BaTiO3 based sensing film is prepared at room temperature, then post-annealed at 200 °C and 400 °C to enhance material's sensing properties. Thermal exposure of BaTiO3 sensing film increases electron density, improves material defects, enhances grain to grain connectivity, and escalates hydrophilicity. The sensitivity of all fabricated devices is evaluated by comparing capacitive variation at different relative humidity (RH) levels. The electric field distribution and open area ratio (OAR) are scrutinized to understand the effect of these parameters on the BaTiO3 integrated capacitive type humidity sensor. The obtained results indicate that the IDC-1 with large OAR reveals high sensitivity due to the availability of the wider interaction area between fringing electric field intensity and water vapors adsorbed on sensing material surface. Similarly, the SSC structure reveals high sensitivity over IDC-2 and IDC-3 due to the existence of concentrated electric field intensity and large OAR. The intensified electric field polarizes the water vapor molecules and sensing material ions that upsurge the device capacitance at various RH levels, which enhances sensitivity. This study reveals that the design structure, electric field intensity, and sensing material property are equally responsible for high sensitivity in capacitive humidity sensors.